Anti-degumming CCS heat sealing film and preparation method thereof

The CCS hot seal film employs a UV-curable adhesive blend to address adhesion and thermal sealing challenges, achieving robust and durable interfaces for improved battery system reliability.

CN119684927APending Publication Date: 2025-03-25GUANGDONG LEARY NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411954764.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing CCS hot seal films for electric vehicle battery systems face issues with poor adhesion, thermal sealing performance, and susceptibility to delamination and blistering due to inadequate interfacial interactions between the hot melt adhesive and substrate, as well as challenges in balancing thermal sealing and anti-bleeding properties.

Method used

A CCS hot seal film with a UV-curable hot melt adhesive composition comprising a blend of saturated polyester resins with varying glass transition temperatures, non-saturated acrylic resins, and ring-opening resins, along with additives like blockers and titanium dioxide, which form a stable and durable interface through controlled cross-linking and molecular interactions, ensuring strong adhesion and thermal stability.

Benefits of technology

The solution provides a CCS hot seal film with enhanced adhesion, thermal sealing performance, and anti-bleeding properties, maintaining stability under varying temperatures and humidity conditions, thus ensuring the reliability and longevity of the battery system.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The anti-degumming CCS heat sealing film comprises a base material and a hot melt adhesive layer which are sequentially connected from bottom to top, and the hot melt adhesive layer is obtained by UV curing of UV hot melt adhesive coated on the base material; the UV hot melt adhesive comprises the following components in parts by mass: 15-20 parts of saturated polyester resin I, 5-15 parts of saturated polyester resin II, 30-45 parts of unsaturated acrylate resin, 2-10 parts of epoxy resin, 1-8 parts of a photoinitiator and 50-70 parts of a solvent, the saturated polyester resin I is semi-crystalline resin, and the glass transition temperature of the saturated polyester resin I is-35 to 15 DEG C; the saturated polyester resin II is linear resin, and the glass transition temperature of the saturated polyester resin II is 50-120 DEG C. The anti-degumming CCS heat sealing film provided by the invention can simultaneously have heat sealing performance and glue overflow resistance on the premise of having excellent anti-degumming performance, and has excellent and lasting metal adhesion performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of film manufacturing, and in particular to an anti-debonding CCS heat-sealing film and a preparation method thereof. Background Art

[0002] The cell connection system (abbreviated as "CCS module" or "CCS") is an electrical connection structure within the battery module. It integrates information acquisition components (such as wiring harnesses, PCB, FPC, FFC, etc.), plastic structural parts, aluminum bars and other components to achieve electrical connection and communication between battery cells, monitor the battery status, and ensure the safe and efficient operation of the battery module. It is widely used in new energy vehicles and energy storage systems.

[0003] In the battery cell connection system, CCS heat sealing film plays a vital role. The main functions of CCS heat sealing film are as follows: (1) Through the heat sealing process, the battery cell, signal acquisition components (such as FPC, PCB, etc.) and aluminum busbars are tightly packaged together to form a stable electrical connection. (2) It has good sealing performance, which can prevent impurities such as moisture and dust from entering the battery module, ensuring the safety and reliability of the battery; (3) It usually has good insulation impedance performance, which can prevent safety problems caused by current leakage or short circuit during the battery charging and discharging process; (4) In the battery module, it provides stable support for the battery cell to prevent the battery cell from being damaged due to expansion or contraction during the charging and discharging process.

[0004] The existing CCS heat-sealing film mainly includes a substrate and a hot-melt adhesive layer obtained by coating UV hot-melt adhesive on the substrate and curing it. The performance of the CCS heat-sealing film mainly depends on the characteristics of the hot-melt adhesive layer. Although the existing hot-melt adhesive layer is widely used, it still has many shortcomings: (1) There are differences in the adhesion of the hot-melt adhesive layer to different substrates, which leads to the problem of the hot-melt adhesive layer easily falling off from the surface of the substrate in some application scenarios (i.e., the anti-debonding performance is poor), which not only affects the electrical connection stability of the battery cell connection system, but also may pose a threat to the safety of the battery module. (2) The cross-linking degree of the hot-melt adhesive layer is crucial to the heat-sealing performance of the CCS heat-sealing film. However, if the cross-linking degree is too high, the CCS heat-sealing film will be too hard and the heat-sealing performance will be poor; if the cross-linking degree is too low, the rheological rate of the UV hot-melt adhesive will increase, causing the problem of glue overflow and poor anti-glue overflow performance. Therefore, it is difficult for CCS heat-sealing film to take into account both heat-sealing performance and anti-glue overflow performance. (3) Existing UV hot melt adhesives generally use saturated polyester resin as the main resin. However, the ester group in the saturated polyester resin is easily hydrolyzed, which makes the saturated polyester resin easily swell under the action of water vapor in the natural environment, making the hot melt adhesive layer prone to cracking or bubbles in the adhesive layer. This not only leads to poor adhesion between the substrate and the hot melt adhesive layer, further deteriorating the anti-debonding performance, but also causes the hot melt adhesive layer to have a reduced metal bonding performance on components such as aluminum bars, making it difficult to meet the use requirements of long-term metal bonding. Summary of the invention

[0005] The purpose of the present invention is to provide an anti-debonding CCS heat-sealing film, which has excellent anti-debonding performance, heat-sealing performance and anti-glue overflow performance, and has excellent and lasting metal bonding performance, so as to overcome the shortcomings of the prior art.

[0006] The second purpose of the present invention is to provide a preparation method of an anti-debonding CCS heat-sealing film. The preparation method is simple and easy to operate, ensuring that the obtained CCS heat-sealing film has both heat-sealing performance and anti-glue overflow performance while having excellent anti-debonding performance, and has excellent and lasting metal adhesion performance to meet actual use requirements.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] An anti-debonding CCS heat-sealing film, comprising a substrate and a hot-melt adhesive layer connected in sequence from bottom to top, wherein the hot-melt adhesive layer is obtained by UV hot-melt adhesive coated on the substrate and cured by UV;

[0009] Calculated by weight, the UV hot melt adhesive includes 15-20 parts of saturated polyester resin I, 5-15 parts of saturated polyester resin II, 30-45 parts of unsaturated acrylate resin, 2-10 parts of epoxy resin, 1-8 parts of photoinitiator and 50-70 parts of solvent;

[0010] The saturated polyester resin I is a semi-crystalline resin, and the glass transition temperature of the saturated polyester resin I is -35 to 15°C;

[0011] The saturated polyester resin II is a linear resin, and the glass transition temperature of the saturated polyester resin II is 50 to 120°C.

[0012] Furthermore, the crystallinity of the saturated polyester resin I is 10-30%, and the glass transition temperature of the saturated polyester resin I is 5-10°C;

[0013] The glass transition temperature of the saturated polyester resin II is 70-100°C.

[0014] Furthermore, the epoxy resin is bisphenol A epoxy resin.

[0015] Furthermore, the molecular weight of the unsaturated acrylic resin is 2500-10000.

[0016] Furthermore, the unsaturated acrylate resin includes any one of an unsaturated polyurethane acrylate resin and an unsaturated polyether acrylate resin.

[0017] Furthermore, the UV hot melt adhesive also includes a flame retardant, an anti-adhesive agent and titanium dioxide;

[0018] Calculated by mass, the UV hot melt adhesive includes 15-20 parts of saturated polyester resin I, 5-15 parts of saturated polyester resin II, 30-45 parts of unsaturated acrylate resin, 2-10 parts of epoxy resin, 1-8 parts of photoinitiator, 10-25 parts of flame retardant, 0.5-3 parts of anti-blocking agent, 1-3 parts of titanium dioxide and 50-70 parts of solvent.

[0019] Furthermore, the anti-adhesive agent includes any one of wax powder and silicon powder.

[0020] Furthermore, the thickness of the substrate is 25 to 50 μm; the thickness of the hot melt adhesive layer is 25 to 100 μm.

[0021] A method for preparing an anti-degumming CCS heat-sealing film, characterized in that the method is used to prepare the above-mentioned anti-degumming CCS heat-sealing film, comprising the following steps:

[0022] A. uniformly mixing the formulated amounts of saturated polyester resin I, saturated polyester resin II, unsaturated acrylic resin and solvent to obtain a first mixed material;

[0023] B. adding the flame retardant, anti-blocking agent and titanium dioxide in the formulated amount to the first mixed material, stirring and grinding to obtain a second mixed material;

[0024] C. adding a formulated amount of epoxy resin to the second mixed material, stirring and filtering to obtain a third mixed material;

[0025] D. adding a formulated amount of photoinitiator to the third mixed material to obtain a UV hot melt adhesive;

[0026] E. UV hot melt adhesive is coated on the surface of the substrate, and a hot melt adhesive layer is formed on the surface of the substrate after UV curing to obtain an anti-debonding CCS heat sealing film.

[0027] Furthermore, step E specifically includes: performing corona treatment on the surface of the substrate, coating the corona treated surface of the substrate with UV hot melt adhesive, and forming a hot melt adhesive layer on the surface of the substrate after UV curing to obtain an anti-debonding CCS heat-sealing film.

[0028] The technical solution provided by the present invention may include the following beneficial effects:

[0029] 1. Through the cross-linking and curing reaction of unsaturated acrylic resin and epoxy resin, and the intermolecular force between the ester groups in saturated polyester resin I and saturated polyester resin II and the polar groups in the substrate, even if the UV hot melt adhesive contains saturated polyester resin I and saturated polyester resin II, the hot melt adhesive layer formed after the UV hot melt adhesive is cured can form a strong adhesion with the substrate, avoiding the problem of the hot melt adhesive layer falling off from the surface of the substrate, thereby ensuring the anti-debonding performance.

[0030] 2. The glass transition temperature of saturated polyester resin I is 35-15°C, and the glass transition temperature of saturated polyester resin II is 50-120°C. If only saturated polyester resin I is added to the UV hot melt adhesive formula, the overall glass transition temperature of the UV hot melt adhesive will be too low. Too low a glass transition temperature means that the UV hot melt adhesive can be transformed from a glassy state to a highly elastic state at a relatively low temperature, making the hot melt adhesive layer too soft and prone to overflow. At the same time, too low a glass transition temperature also means too low a heat sealing temperature, resulting in insufficient bonding strength between the hot melt adhesive layer and the substrate, affecting the heat sealing performance. At the same time, if only saturated polyester resin II is added to the UV hot melt adhesive formula, the overall glass transition temperature of the UV hot melt adhesive is too high. Too high a glass transition temperature means that the UV hot melt adhesive needs to be at a higher temperature to be transformed from a glassy state to a highly elastic state, resulting in the heat sealing temperature of the CCS heat sealing film being too high and the heat sealing performance being reduced. Therefore, the present technical solution uses saturated polyester resin I and saturated polyester resin II in combination, so that the heat sealing temperature of the CCS heat sealing film is maintained at 100-180°C, and the hot melt adhesive layer has moderate hardness and softness, and is not prone to glue overflow.

[0031] 3. In the technical solution, the unsaturated acrylic resin can undergo a cross-linking and curing reaction with the epoxy resin to form a cross-linked product, which has a three-dimensional structure and can wrap the ester groups in the saturated polyester resin I and the saturated polyester resin II, thereby limiting the hydrolysis of the ester groups in the saturated polyester resin I and the saturated polyester resin II, and avoiding the adverse effects caused by the hydrolysis of the ester groups in the saturated polyester resin I and the saturated polyester resin II, thereby ensuring that the CCS heat-sealing film has a long-lasting metal adhesion. DETAILED DESCRIPTION

[0032] The present technical solution provides an anti-debonding CCS heat-sealing film, comprising a substrate and a hot-melt adhesive layer connected in sequence from bottom to top, wherein the hot-melt adhesive layer is obtained by UV hot-melt adhesive coated on the substrate and cured by UV;

[0033] Calculated by weight, the UV hot melt adhesive includes 15-20 parts of saturated polyester resin I, 5-15 parts of saturated polyester resin II, 30-45 parts of unsaturated acrylate resin, 2-10 parts of epoxy resin, 1-8 parts of photoinitiator and 50-70 parts of solvent;

[0034] The saturated polyester resin I is a semi-crystalline resin, and the glass transition temperature of the saturated polyester resin I is -35 to 15°C;

[0035] The saturated polyester resin II is a linear resin, and the glass transition temperature of the saturated polyester resin II is 50 to 120°C.

[0036] In view of the shortcomings of the existing CCS heat-sealing film that it is difficult to meet the actual use needs, this scheme proposes an anti-debonding CCS heat-sealing film, including a substrate and a hot-melt adhesive layer connected in sequence from bottom to top. By optimizing the UV hot-melt adhesive and the curing process, the CCS heat-sealing film can have both heat-sealing performance and anti-glue overflow performance while having excellent anti-debonding performance, and has excellent and long-lasting metal adhesion performance, thus meeting the actual use needs.

[0037] Specifically, the raw materials of UV hot melt adhesive include saturated polyester resin I, saturated polyester resin II, unsaturated acrylate resin, epoxy resin, photoinitiator and solvent. Among them, under UV light irradiation, unsaturated acrylate resin as UV curing photosensitive prepolymer, under the action of photoinitiator, can undergo cross-linking and curing reaction with epoxy groups in epoxy resin, and the formed cross-linked product can effectively improve the bonding strength of the hot melt adhesive layer and increase the adhesion between the substrate and the hot melt adhesive layer.

[0038] In addition, the raw materials of UV hot melt adhesive also include saturated polyester resin I and saturated polyester resin II. Both saturated polyester resin I and saturated polyester resin II contain ester groups, and the substrates used in existing CCS heat sealing films (such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and polyethylene naphthalate (PEN)) generally contain ester groups. Polyimide (PI) contains amide groups and imide groups, and ester groups, amide groups and imide groups are all polar groups. There is a strong intermolecular force between the polar groups, which is conducive to the formation of firm adhesion between the hot melt adhesive layer and the substrate. That is, through the cross-linking and curing reaction of unsaturated acrylic resin and epoxy resin, and the mutual coordination of the intermolecular force between the ester groups in saturated polyester resin I and saturated polyester resin II and the polar groups in the substrate, even if the UV hot melt adhesive contains saturated polyester resin I and saturated polyester resin II, the hot melt adhesive layer formed after the UV hot melt adhesive is cured can form a strong adhesion with the substrate, avoiding the problem of the hot melt adhesive layer falling off from the surface of the substrate, thereby ensuring the anti-debonding performance.

[0039] Secondly, the glass transition temperature of saturated polyester resin I is 35-15°C, and the glass transition temperature of saturated polyester resin II is 50-120°C. If only saturated polyester resin I is added to the UV hot melt adhesive formula, the overall glass transition temperature of the UV hot melt adhesive will be too low. Too low a glass transition temperature means that the UV hot melt adhesive can be transformed from a glassy state to a highly elastic state at a relatively low temperature, making the hot melt adhesive layer too soft and prone to glue overflow. At the same time, too low a glass transition temperature also means too low a heat sealing temperature, resulting in insufficient bonding strength between the hot melt adhesive layer and the substrate, affecting the heat sealing performance.

[0040] At the same time, if only saturated polyester resin II is added to the UV hot melt adhesive formula, the overall glass transition temperature of the UV hot melt adhesive is too high. The excessively high glass transition temperature means that the UV hot melt adhesive needs to be at a higher temperature to transform from the glass state to the highly elastic state, resulting in the heat sealing temperature of the CCS heat sealing film being too high and the heat sealing performance being reduced. Therefore, this technical solution uses saturated polyester resin I and saturated polyester resin II together to maintain the heat sealing temperature of the CCS heat sealing film at 100-180°C, and the hot melt adhesive layer is moderately soft and hard, and it is not easy to overflow the glue.

[0041] In addition, the heat sealing performance and anti-glue overflow performance of CCS heat sealing film are also greatly affected by the crosslinking degree of unsaturated acrylic resin and epoxy resin. Specifically, if the crosslinking degree is too high, the CCS heat sealing film will be too hard and the heat sealing performance will be poor; if the crosslinking degree is too low, the rheological rate of UV hot melt adhesive will increase, causing glue overflow problems and poor anti-glue overflow performance. Therefore, in this technical solution, the addition amount of unsaturated acrylic resin is limited to 30-45 parts, the addition amount of epoxy resin is limited to 2-10 parts, and the addition amount of photoinitiator is limited to 1-8 parts, so that the crosslinking and curing degree of unsaturated acrylic resin and epoxy resin is moderate, so that CCS heat sealing film can take into account both heat sealing performance and anti-glue overflow performance. That is, this technical solution cooperates with saturated polyester resin I and saturated polyester resin II, and limits the addition amount of unsaturated acrylic resin, epoxy resin and photoinitiator, so that CCS heat sealing film can take into account both heat sealing performance and anti-glue overflow performance.

[0042] Secondly, saturated polyester resin II is a linear resin. This structure makes the molecular chain of saturated polyester resin II more flexible and easy to spread on the metal surface to form a uniform covering layer. At the same time, the linear structure is also conducive to the interaction between saturated polyester resin II molecules and atoms or molecules on the metal surface, forming chemical bonds or physical adsorption, thereby enhancing the metal adhesion. In addition, the glass transition temperature of saturated polyester resin II is 50-120°C. Saturated polyester resin II is in a higher energy state at room temperature, and the molecular chain movement is more active. It is easy to interact and react with the metal surface, thus having a higher metal adhesion. That is, by limiting the structure and glass transition temperature of saturated polyester resin II, it is beneficial to give the CCS heat-sealing film a higher metal adhesion.

[0043] In addition, in the prior art, UV hot melt adhesive is generally a thermosetting UV hot melt adhesive, but the metal bonding performance of the thermosetting UV hot melt adhesive is greatly affected by the curing temperature (i.e., the external temperature). Specifically, when the curing temperature is too high, the UV hot melt adhesive cures too quickly, and the uniformity of the curing degree is poor, which affects the metal bonding performance; when the curing temperature is too low, the curing degree of the UV hot melt adhesive is limited, which also affects the metal bonding performance. The present technical solution uses UV hot melt adhesive, which is cured by UV curing (i.e., curing after ultraviolet light irradiation) rather than thermal curing. The degree of curing is less related to the external temperature, so that even in an environment with large changes in external temperature, the degree of curing can be ensured by adjusting the ultraviolet irradiation time and intensity, thereby ensuring the metal bonding performance. In addition, since the UV hot melt adhesive is cured by UV curing rather than thermal curing, it is not easily affected by high temperature and deteriorates during storage, which improves the storage stability of the UV hot melt adhesive in a high temperature environment.

[0044] Furthermore, although the performance parameters of saturated polyester resin II are optimized and the UV hot melt adhesive with UV curing is used to ensure the metal bonding property of CCS heat sealing film, the ester group in saturated polyester resin is easy to hydrolyze, which makes the saturated polyester resin easy to swell under the action of water vapor in the natural environment, making the hot melt adhesive layer easy to crack or bubbles appear in the adhesive layer, resulting in that even if the performance parameters of saturated polyester resin II and the curing method of hot melt adhesive are optimized, it is difficult to meet the use requirements of CCS heat sealing film with long-lasting metal bonding property. In the present technical solution, the unsaturated acrylic resin can undergo cross-linking and curing reaction with epoxy resin to form a cross-linked product, which has a three-dimensional structure and can wrap the ester group in saturated polyester resin I and saturated polyester resin II, limiting the hydrolysis of the ester group in saturated polyester resin I and saturated polyester resin II, avoiding the adverse effects of the hydrolysis of the ester group in saturated polyester resin I and saturated polyester resin II, thereby ensuring that the CCS heat sealing film has long-lasting metal bonding property.

[0045] Finally, saturated polyester resin I is a semi-crystalline resin. This structure makes the internal molecular arrangement of saturated polyester resin I more orderly, forming a certain crystalline region. The above-mentioned crystalline region is conducive to improving the density and stability of saturated polyester resin I, thereby reducing the movement and leakage of charges inside saturated polyester resin I and enhancing insulation resistance. In addition, the glass transition temperature of saturated polyester resin I is between -35 and 15°C, so that saturated polyester resin I is in a glassy state at room temperature, the movement of molecular chains is restricted, and it is not easy to deform and move charges, and it also has good insulation resistance. That is, by limiting the two parameters of molecular structure and glass transition temperature of saturated polyester resin I, it is given insulation resistance performance to meet the insulation resistance performance requirements of CCS heat sealing film.

[0046] Preferably, the solvent includes toluene and butanone.

[0047] Toluene has good solubility and a low boiling point, and is easy to volatilize; while butanone also has excellent solubility, with a moderate boiling point and a balanced volatilization rate, which is conducive to effectively maintaining the stability of the system during the coating or curing process. Therefore, this technical solution uses toluene and butanone as the solvent system. This combination can not only efficiently dissolve the raw materials to form a uniform UV hot melt adhesive solution, which is conducive to the uniform coating of the UV hot melt adhesive on the substrate, but also during the UV curing process, the orderly volatilization of toluene and butanone promotes the gradual curing of the UV hot melt adhesive, effectively avoiding the generation of bubbles and cracks during the UV curing process, thereby greatly improving the curing quality.

[0048] Preferably, the substrate is any one of a PET film and a PI film.

[0049] It should be noted that the photoinitiator can be 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), 1-hydroxycyclohexylphenyl ketone (184), 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone (907) and 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone (369), and the specific types are not limited here.

[0050] It is further described that the crystallinity of the saturated polyester resin I is 10-30%, and the glass transition temperature of the saturated polyester resin I is 5-10°C;

[0051] The glass transition temperature of the saturated polyester resin II is 70-100°C.

[0052] Further limiting the performance parameters of saturated polyester resin I and saturated polyester resin II is more conducive to ensuring the performance of CCS heat-sealing film.

[0053] It is further specified that the epoxy resin is bisphenol A epoxy resin.

[0054] After curing, bisphenol A epoxy resin has high strength and toughness, and can withstand large external forces without being easily broken or deformed, so that the hot melt adhesive layer has excellent adhesion and durability, which is beneficial to ensuring the performance of CCS heat sealing film; in addition, bisphenol A epoxy resin has excellent electrical insulation properties, which is beneficial to improving the insulation impedance performance of CCS heat sealing film.

[0055] It is further described that the molecular weight of the unsaturated acrylic resin is 2500-10000.

[0056] By limiting the molecular weight of the unsaturated acrylic resin, the process of cross-linking and curing reaction between the unsaturated bonds in the unsaturated acrylic resin and the epoxy groups in the epoxy resin can be more controllable, which is conducive to forming a stable three-dimensional network structure, thereby improving the performance of the product.

[0057] To further illustrate, the unsaturated acrylate resin includes any one of an unsaturated polyurethane acrylate resin and an unsaturated polyether acrylate resin.

[0058] Both unsaturated polyurethane acrylate resin and unsaturated polyether acrylate resin can be cured quickly under the action of ultraviolet light, and the curing speed is fast, which is conducive to improving production efficiency. In addition, both unsaturated polyurethane acrylate resin and unsaturated polyether acrylate resin have high strength and toughness, can withstand large external impact and stretching, and are not prone to breakage or deformation, so that the hot melt adhesive layer has excellent adhesion and durability, ensuring the performance of CCS heat sealing film.

[0059] It should be noted that the unsaturated polyurethane acrylate resin may be Sartomer CN965, Corning 6008 and Cytec EB5129, and the specific types are not limited here.

[0060] In addition, the unsaturated polyether acrylate resin may be Sartomer CN501, Corning 5025F and BASF LR8967, and the specific types are also not limited here.

[0061] It is further explained that the UV hot melt adhesive also includes a flame retardant, an anti-adhesive agent and titanium dioxide;

[0062] Calculated by mass, the UV hot melt adhesive includes 15-20 parts of saturated polyester resin I, 5-15 parts of saturated polyester resin II, 30-45 parts of unsaturated acrylate resin, 2-10 parts of epoxy resin, 1-8 parts of photoinitiator, 10-25 parts of flame retardant, 0.5-3 parts of anti-blocking agent, 1-3 parts of titanium dioxide and 50-70 parts of solvent.

[0063] UV hot melt adhesive also includes flame retardants, anti-adhesives and titanium dioxide. Among them, flame retardants can increase the flame retardancy of UV hot melt adhesive and meet the flame retardancy requirements of CCS heat sealing film; anti-adhesives are helpful to prevent adhesion between adjacent CCS heat sealing films during the winding process, ensuring the cleanliness and separation between CCS heat sealing films; titanium dioxide has good whiteness and glossiness, which can make CCS heat sealing film present a purer and brighter appearance, ensuring the appearance of CCS heat sealing film. In addition, titanium dioxide has good weather resistance and UV resistance, which can effectively prevent CCS heat sealing film from discoloring and aging in outdoor environments, which is helpful to extend the service life of CCS heat sealing film.

[0064] Preferably, the flame retardant includes any one or more combinations of brominated flame retardants, phosphorus flame retardants, and nitrogen flame retardants;

[0065] The brominated flame retardant includes any one or more combinations of polybrominated diphenyl ethers, tribromophenols, brominated phthalic anhydrides, brominated bisphenol A, brominated alcohols, and brominated polymers;

[0066] The phosphorus-based flame retardant includes any one or more combinations of triphenyl phosphate, ethylphenyl phenyl phosphate, tert-butylphenyl diyl phosphate, tetraaryl arylene bisphosphate, resorcinol phosphate and tetraphenyl bisphenol A-diphosphate;

[0067] The nitrogen-based flame retardant includes any one or more combinations of melamine, cyanuric acid, dicyandiamide, thiourea, urea and derivatives thereof.

[0068] It is further described that the anti-adhesive agent includes any one of wax powder and silicon powder.

[0069] When adjacent CCS heat-sealing films are close to each other, especially when heated and squeezed, wax powder can significantly reduce the tendency of adhesion between the two. In addition, silicon powder can form many tiny protrusions on the surface of CCS heat-sealing films, increase the surface roughness of CCS heat-sealing films, and thus effectively prevent the mutual adhesion between adjacent CCS heat-sealing films. Therefore, the anti-adhesion agent of the technical solution includes any one of wax powder and silicon powder, which is conducive to avoiding the adhesion of CCS heat-sealing films and ensuring the convenience of winding and use.

[0070] It is further described that the thickness of the substrate is 25 to 50 μm; the thickness of the hot melt adhesive layer is 25 to 100 μm.

[0071] The thickness of the substrate is 25-50 μm, which plays a certain supporting role and ensures the strength and hardness of the CCS heat-sealing film. In addition, if the thickness of the hot-melt adhesive layer is too thin, the metal adhesion force is likely to decrease; if the thickness of the hot-melt adhesive layer is too thick, the anti-overflow performance becomes poor and the cost is too high. Therefore, the technical solution limits the thickness of the hot-melt adhesive layer to 25-100 μm, which is conducive to ensuring the performance of the CCS heat-sealing film.

[0072] A method for preparing an anti-degumming CCS heat-sealing film, used for preparing the above-mentioned anti-degumming CCS heat-sealing film, comprises the following steps:

[0073] A. uniformly mixing the formulated amounts of saturated polyester resin I, saturated polyester resin II, unsaturated acrylic resin and solvent to obtain a first mixed material;

[0074] B. adding the flame retardant, anti-blocking agent and titanium dioxide in the formulated amount to the first mixed material, stirring and grinding to obtain a second mixed material;

[0075] C. adding a formulated amount of epoxy resin to the second mixed material, stirring and filtering to obtain a third mixed material;

[0076] D. adding a formulated amount of photoinitiator to the third mixed material to obtain a UV hot melt adhesive;

[0077] E. UV hot melt adhesive is coated on the surface of the substrate, and a hot melt adhesive layer is formed on the surface of the substrate after UV curing to obtain an anti-debonding CCS heat sealing film.

[0078] The technical solution also proposes a method for preparing an anti-debonding CCS heat-sealing film. The preparation method is simple and easy to operate, ensuring that the obtained CCS heat-sealing film not only has excellent anti-debonding performance, but also has both heat-sealing performance and anti-glue overflow performance, and also has excellent and long-lasting metal adhesion performance, thus meeting actual use requirements.

[0079] Preferably, in step A, the stirring speed is 500-1000 r / min, and the stirring time is 5-10 min;

[0080] In step B, the stirring speed is 800-1200 r / min, and the stirring time is 5-10 min; the grinding time is 30-50 min;

[0081] In step C, the mesh size of the filtration is 150 to 200 meshes.

[0082] By limiting the stirring speed and stirring time in step A and step B, it is beneficial to promote the mixing uniformity of the raw materials and ensure the performance of the UV hot melt adhesive. In addition, grinding is conducive to further refining the particles, improving the fineness and uniformity of the raw materials, thereby improving the appearance and performance of the final product. Limiting the grinding time to 30 to 50 minutes can ensure that the grinding process will not be damaged or deteriorated due to excessive grinding. Furthermore, filtering with a 150-200 mesh filter can remove large particle impurities in the third mixture and ensure the purity and uniformity of the UV hot melt adhesive.

[0083] To further illustrate, step E specifically comprises: performing corona treatment on the surface of the substrate, coating the corona treated surface of the substrate with UV hot melt adhesive, and forming a hot melt adhesive layer on the surface of the substrate after UV curing to obtain an anti-debonding CCS heat sealing film.

[0084] The technical solution performs corona treatment on the surface of the substrate, which is beneficial to increasing the adhesion of the substrate surface to the hot melt adhesive layer, thereby improving the anti-debonding performance.

[0085] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0086] Performance Test:

[0087] 1. Heat sealing performance: Cut the CCS heat sealing film into CCS heat sealing film samples with a width of 15mm, and heat seal the aluminum alloy plate with a thickness of 0.5mm under the conditions of temperature of 180℃, pressure of 0.5Mpa, and roller speed of 1m / min to observe whether the CCS heat sealing film sample can heat seal the aluminum alloy plate. If heat sealing can be achieved, the heat sealing performance is qualified; otherwise, the heat sealing performance is unqualified.

[0088] 2. Anti-debonding performance: CCS heat-sealing film is cut into CCS heat-sealing film samples with a width of 15mm. The UV hot melt adhesive surfaces of two CCS heat-sealing film samples are bonded together at a temperature of 180℃ and a pressure of 0.5Mpa for 3s to obtain the test samples. The peel strength of the test samples at -20℃, 25℃ and 85℃ is tested by a tensile machine. In addition, the test samples are placed at a temperature of 85℃ and a relative humidity of 85% for 1000h, and then the peel strength at 25℃ is tested. If the substrate of the test sample is damaged at -20℃, 25℃ and after being placed for 1000h, and the peel strength of the test sample at 85℃ is greater than 8.5N, the anti-debonding performance is qualified; otherwise, the anti-debonding performance is unqualified.

[0089] 3. Metal bonding performance: CCS heat sealing film is cut into CCS heat sealing film samples with a width of 15mm, and heat-sealed with aluminum alloy plates with a thickness of 0.5mm under the conditions of temperature of 180℃, pressure of 0.5Mpa, and roller speed of 1m / min to obtain test samples. The peel strength of the test samples at -20℃, 25℃ and 85℃ is tested by a tensile machine; if the substrate of the test sample is damaged at -20℃ and 25℃, and the peel strength of the test sample at 85℃ is greater than 11N, the metal bonding performance is qualified; otherwise, the metal bonding performance is unqualified.

[0090] 4. Metal adhesion durability: Cut the CCS heat-sealing film into CCS heat-sealing film samples with a width of 15mm, and heat-seal the aluminum alloy plate with a thickness of 0.5mm under the conditions of temperature of 180℃, pressure of 0.5Mpa, and roller speed of 1m / min to obtain the test sample. Place the test sample at a temperature of 85℃ and a relative humidity of 85% for 2000h, and observe whether the hot melt adhesive layer of the test sample has cracks, bubbles, or delamination from the aluminum alloy plate. If there is no such phenomenon, the metal adhesion durability is good; otherwise, the metal adhesion durability is unqualified.

[0091] 5. Glue overflow performance: CCS heat-sealing film was cut into CCS heat-sealing film samples with a width of 15 mm, and heat-sealed with aluminum alloy plates with a thickness of 0.5 mm at a temperature of 180°C, a pressure of 0.5 MPa, and a roller speed of 1 m / min to obtain test samples. After the test samples were placed in an oven at 125°C for 96 hours, the surface of the aluminum alloy plates was observed to see if there was any UV hot melt adhesive overflowing. If there was no UV hot melt adhesive overflowing, the anti-glue overflow performance was qualified; otherwise, the anti-glue overflow performance was unqualified.

[0092] 6. Storage stability: After the CCS heat-sealing film is placed at 70°C for 7 days, a test sample is obtained. The penetration depth of the hot melt adhesive layer of the test sample is detected by a thermomechanical analyzer (TMA) under the test condition of Fcc: -700mN. If the penetration depth is less than 66μm, the storage stability is qualified; otherwise, the storage stability is unqualified.

[0093] Example 1

[0094] A. 15 parts of saturated polyester resin I, 10 parts of saturated polyester resin II, 35 parts of unsaturated acrylic resin and 50 parts of solvent were stirred at a speed of 800 r / min for 8 minutes to obtain a first mixture; saturated polyester resin I was a semi-crystalline resin with a crystallinity of 15% and a glass transition temperature of 15°C; saturated polyester resin II was a linear resin with a glass transition temperature of 70°C; the mass mixing ratio of toluene and butanone in the solvent was 3:1; the unsaturated acrylic resin was Sartomer CN965;

[0095] B. adding 15 parts of triphenyl phosphate, 2 parts of wax powder and 1 part of titanium dioxide to the first mixture, stirring at a speed of 800 r / min for 5 minutes, and grinding to obtain a second mixture;

[0096] C. adding 4 parts of bisphenol A epoxy resin to the second mixture, stirring and filtering with a 150-mesh filter to obtain a third mixture;

[0097] D. adding 3 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone to the third mixed material to obtain a UV hot melt adhesive;

[0098] E. The surface of the PET film with a thickness of 50 μm is subjected to corona treatment, and UV hot melt adhesive is coated on the surface of the PET film after the corona treatment. After UV curing, a hot melt adhesive layer with a thickness of 50 μm is formed on the surface of the PET film to obtain an anti-debonding CCS heat-sealing film.

[0099] Example 2

[0100] A. 20 parts of saturated polyester resin I, 10 parts of saturated polyester resin II, 35 parts of unsaturated acrylic resin and 60 parts of solvent were stirred at a speed of 1000 r / min for 10 minutes to obtain a first mixed material; saturated polyester resin I is a semi-crystalline resin with a crystallinity of 20% and a glass transition temperature of -20°C; saturated polyester resin II is a linear resin with a glass transition temperature of 80°C; the mass mixing ratio of toluene and butanone in the solvent is 2:1; the unsaturated acrylic resin is Corning 5025F;

[0101] B. adding 15 parts of cyanuric acid, 1 part of silicon powder and 1 part of titanium dioxide to the first mixture, stirring at a speed of 1000 r / min for 7 minutes, and grinding to obtain a second mixture;

[0102] C. adding 5 parts of bisphenol A epoxy resin to the second mixture, stirring and filtering with a 200-mesh filter to obtain a third mixture;

[0103] D. adding 3 parts of 1-hydroxycyclohexyl phenyl ketone to the third mixed material to obtain a UV hot melt adhesive;

[0104] E. The surface of the PET film with a thickness of 50 μm is subjected to corona treatment, and UV hot melt adhesive is coated on the surface of the PET film after the corona treatment. After UV curing, a hot melt adhesive layer with a thickness of 60 μm is formed on the surface of the PET film to obtain an anti-debonding CCS heat-sealing film.

[0105] Example 3

[0106] A. 18 parts of saturated polyester resin I, 12 parts of saturated polyester resin II, 40 parts of unsaturated acrylic resin and 50 parts of solvent were stirred at a speed of 500 r / min for 10 minutes to obtain a first mixture; saturated polyester resin I is a semi-crystalline resin with a crystallinity of 30% and a glass transition temperature of 15°C; saturated polyester resin II is a linear resin with a glass transition temperature of 70°C; the mass mixing ratio of toluene and butanone in the solvent is 1:1; the unsaturated acrylic resin is BASF LR8967;

[0107] B. adding 10 parts of ethylphenyl phenyl phosphate, 0.5 parts of wax powder and 3 parts of titanium dioxide to the first mixture, stirring at a speed of 1200 r / min for 5 minutes, and grinding to obtain a second mixture;

[0108] C. adding 5 parts of bisphenol A epoxy resin to the second mixture, stirring and filtering with a 180-mesh filter to obtain a third mixture;

[0109] D. adding 4 parts of 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinebenzylphenyl)butanone to the third mixed material to obtain a UV hot melt adhesive;

[0110] E. The surface of the PI film with a thickness of 25 μm is subjected to corona treatment, and UV hot melt adhesive is coated on the surface of the PI film after the corona treatment. After UV curing, a hot melt adhesive layer with a thickness of 45 μm is formed on the surface of the PI film to obtain an anti-debonding CCS heat-sealing film.

[0111] Comparative Example 1

[0112] The preparation method and raw materials of Comparative Example 1 are the same as those of Example 1, except that bisphenol A epoxy resin is not added to the formula of the UV hot melt adhesive in Comparative Example 1.

[0113] Comparative Example 2

[0114] The preparation method and raw materials of Comparative Example 2 are the same as those of Example 1, except that no unsaturated acrylic resin is added to the formula of the UV hot melt adhesive in Comparative Example 2.

[0115] Comparative Example 3

[0116] The preparation method and raw materials of Comparative Example 3 are the same as those of Example 1, except that no saturated polyester resin I is added to the formula of the UV hot melt adhesive in Comparative Example 3.

[0117] CCS heat sealing films were prepared by the preparation methods in the above embodiment and comparative example, and the performance of the CCS heat sealing films was tested. The results are shown in Table 1 below.

[0118] Table 1 Test results of relevant properties of CCS heat sealing film

[0119] Performance test items Heat sealing performance Anti-debonding performance Metal bonding performance Adhesive Metal Persistence Anti-glue overflow performance Storage stability Example 1 qualified qualified qualified qualified qualified qualified Example 2 qualified qualified qualified qualified qualified qualified Example 3 qualified qualified qualified qualified qualified qualified Comparative Example 1 qualified Failure qualified Failure Failure qualified Comparative Example 2 qualified Failure qualified Failure Failure qualified Comparative Example 3 Failure Failure qualified qualified qualified qualified

[0120] From the performance test results in Table 1, it can be seen that the CCS heat-sealing film prepared by the preparation method of an anti-debonding CCS heat-sealing film in the technical scheme has qualified anti-debonding performance, heat sealing performance, anti-glue overflow performance, metal adhesion performance and metal adhesion durability. On the premise of having excellent anti-debonding performance, it can not only have heat sealing performance and anti-glue overflow performance, but also has excellent and durable metal adhesion performance, meeting the use requirements.

[0121] Since no bisphenol A epoxy resin is added in Comparative Example 1 and no unsaturated acrylate resin is added in Comparative Example 2, a cross-linking and curing reaction cannot occur in the system, which not only reduces the adhesion between the substrate and the hot-melt adhesive layer, thereby reducing the anti-debonding performance; but also softens the hot-melt adhesive layer, which is prone to glue overflow; in addition, since no cross-linking product can be formed to wrap the ester groups in the saturated polyester resin I and the saturated polyester resin II, the saturated polyester resin I and the saturated polyester resin II are easily swollen under the action of water vapor in the natural environment, making the hot-melt adhesive layer prone to cracking or bubbles in the adhesive layer, which not only causes the adhesion between the substrate and the hot-melt adhesive layer to deteriorate, further deteriorating the anti-debonding performance, but also affects the durability of metal adhesion.

[0122] In Comparative Example 3, since saturated polyester resin I is not added, not only the adhesion between the hot melt adhesive layer and the substrate is reduced, thereby reducing the anti-debonding performance; but also the heat sealing temperature of the CCS heat-sealing film is too high, and the heat sealing performance is reduced.

[0123] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A debonding-proof CCS heat-sealing film, characterized in that: It includes a substrate and a hot melt adhesive layer connected in sequence from bottom to top, wherein the hot melt adhesive layer is obtained by UV hot melt adhesive coated on the substrate and cured by UV; Calculated by weight, the UV hot melt adhesive includes 15-20 parts of saturated polyester resin I, 5-15 parts of saturated polyester resin II, 30-45 parts of unsaturated acrylate resin, 2-10 parts of epoxy resin, 1-8 parts of photoinitiator and 50-70 parts of solvent; The saturated polyester resin I is a semi-crystalline resin, and the glass transition temperature of the saturated polyester resin I is -35 to 15°C; The saturated polyester resin II is a linear resin, and the glass transition temperature of the saturated polyester resin II is 50-120°C.

2. The anti-debonding CCS heat-sealing film according to claim 1, characterized in that: The crystallinity of the saturated polyester resin I is 10-30%, and the glass transition temperature of the saturated polyester resin I is 5-10°C; The glass transition temperature of the saturated polyester resin II is 70-100°C.

3. The anti-debonding CCS heat-sealing film according to claim 1, characterized in that: The epoxy resin is bisphenol A type epoxy resin.

4. The anti-debonding CCS heat-sealing film according to claim 1, characterized in that: The molecular weight of the unsaturated acrylic resin is 2500-10000.

5. The anti-debonding CCS heat-sealing film according to claim 1, characterized in that: The unsaturated acrylate resin includes any one of an unsaturated polyurethane acrylate resin and an unsaturated polyether acrylate resin.

6. The anti-debonding CCS heat-sealing film according to claim 1, characterized in that: The UV hot melt adhesive also includes a flame retardant, an anti-adhesive agent and titanium dioxide; Calculated by mass, the UV hot melt adhesive includes 15-20 parts of saturated polyester resin I, 5-15 parts of saturated polyester resin II, 30-45 parts of unsaturated acrylate resin, 2-10 parts of epoxy resin, 1-8 parts of photoinitiator, 10-25 parts of flame retardant, 0.5-3 parts of anti-blocking agent, 1-3 parts of titanium dioxide and 50-70 parts of solvent.

7. The anti-debonding CCS heat-sealing film according to claim 6, characterized in that: The anti-adhesive agent includes any one of wax powder and silicon powder.

8. The anti-debonding CCS heat-sealing film according to claim 1, characterized in that: The thickness of the substrate is 25 to 50 μm; the thickness of the hot melt adhesive layer is 25 to 100 μm.

9. A method for preparing an anti-debonding CCS heat-sealing film, characterized in that: The method for preparing the anti-debonding CCS heat-sealing film according to any one of claims 6 to 8 comprises the following steps: A. uniformly mixing the formulated amounts of saturated polyester resin I, saturated polyester resin II, unsaturated acrylic resin and solvent to obtain a first mixed material; B. adding the flame retardant, anti-blocking agent and titanium dioxide in the formula amount to the first mixed material, stirring and grinding to obtain a second mixed material; C. adding a formulated amount of epoxy resin to the second mixed material, stirring and filtering to obtain a third mixed material; D. adding a formulated amount of photoinitiator to the third mixed material to obtain a UV hot melt adhesive; E. UV hot melt adhesive is coated on the surface of the substrate, and a hot melt adhesive layer is formed on the surface of the substrate after UV curing to obtain an anti-debonding CCS heat sealing film.

10. The method for preparing a debonding-resistant CCS heat-sealing film according to claim 9, characterized in that: Step E specifically comprises: performing corona treatment on the surface of the substrate, coating the corona treated surface of the substrate with UV hot melt adhesive, and forming a hot melt adhesive layer on the surface of the substrate after UV curing to obtain an anti-debonding CCS heat sealing film.